Biomonitoring of Ceratopogonidae (Diptera: Nematocera) using car nets - Tóthová, Andrea; Knoz, Jan; Barták, Miroslav; Kubík, Štěpán (Entomologica Fennica, 2005)
Car nets were used to collect two samples on a forest road in Podyji National park, the Braitava forest, Czech Republic. Sampling was done in 2002 between May 31 and June 1, and between July 30 and 31. These consisted of 10 rounds (each 10 km in length) from morning to dusk. Over 3,000 specimens (52 species) of Ceratopogonidae were captured. The results suggest that the car-net method may be efficient in ceratopogonid biomonitoring and e. g. determining their daily flight activity and swarming sites.